2014
DOI: 10.1007/s11673-014-9557-9
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking “Commercial” Surrogacy in Australia

Abstract: This article proposes reconsideration of laws prohibiting paid surrogacy in Australia in light of increasing transnational commercial surrogacy. The social science evidence base concerning domestic surrogacy in developed economies demonstrates that payment alone cannot be used to differentiate "good" surrogacy arrangements from "bad" ones. Compensated domestic surrogacy and the introduction of professional intermediaries and mechanisms such as advertising are proposed as a feasible harm-minimisation approach. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 36 publications
(37 reference statements)
0
26
0
Order By: Relevance
“…As Millbank (2014) notes, a key issue in offshore arrangements is the question of whether in all (or even the majority) of cases true informed consent is given.…”
Section: Conclusion: Ways Forwardmentioning
confidence: 99%
See 3 more Smart Citations
“…As Millbank (2014) notes, a key issue in offshore arrangements is the question of whether in all (or even the majority) of cases true informed consent is given.…”
Section: Conclusion: Ways Forwardmentioning
confidence: 99%
“…With these findings in mind, the paper concludes by considering Millbank's (2014) suggestion that Australian states and territories should legalise onshore commercial surrogacy, and the barriers that may exist to the uptake of such potential legal change.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 It has been suggested that allowing compensated surrogacy in Australia, properly regulated and facilitated by professional recruitment agencies, will not only increase the supply of surrogates, but also improve the quality of medical care, as it allows patients to undertake in vitro fertilisation (IVF) treatment and pregnancy care within the Australian healthcare system. 8 A survey in 1993 reported that only 30% of Australians approved of commercial surrogacy, with 59% disapproving and 11% being undecided. 9 Given the recent large increase in the use of overseas commercial surrogacy services, it was felt appropriate to survey the Australian public's current level of support and concerns, plus their views on what may be considered appropriate compensation for a surrogate.…”
Section: Introductionmentioning
confidence: 99%